Visceral fat inflammation and fat embolism are associated with lung’s lipidic hyaline membranes in subjects with COVID-19 - Colleluori, Georgia; Graciotti, Laura; Pesaresi, Mauro; Di Vincenzo, Angelica; Perugini, Jessica; Di Mercurio, Eleonora; Caucci, Sara; Bagnarelli, Patrizia; Zingaretti, Cristina M.; Nisoli, Enzo; Menzo, Stefano; Tagliabracci, Adriano; et al. (International Journal of Obesity, 2022)
Background Preliminary data suggested that fat embolism could explain the importance of visceral obesity as a critical determinant of coronavirus disease-2019 (COVID-19). Methods We performed a comprehensive histomorphologic analysis of autoptic visceral adipose tissue (VAT), lungs and livers of 19 subjects with COVID-19 (COVID-19+), and 23 people without COVID-19 (controls). Human adipocytes (hMADS) infected with SARS-CoV-2 were also studied. Results Although there were no between-group differences in body-mass-index and adipocytes size, a higher prevalence of CD68+ macrophages among COVID-19+ VAT was detected ( p = 0.005) and accompanied by crown-like structures presence, signs of adipocytes stress and death. Consistently, human adipocytes were successfully infected by SARS-CoV-2 in vitro and displayed lower cell viability. Being VAT inflammation associated with lipids spill-over from dead adipocytes, we studied lipids distribution by ORO. Lipids were observed within lungs and livers interstitial spaces, macrophages, endothelial cells, and vessels lumen, features suggestive of fat embolism syndrome, more prevalent among COVID-19+ ( p < 0.001). Notably, signs of fat embolism were more prevalent among people with obesity ( p = 0.03) independently of COVID-19 diagnosis, suggesting that such condition may be an obesity complication exacerbated by SARS-CoV-2 infection. Importantly, all infected subjects’ lungs presented lipids-rich (ORO+) hyaline membranes, formations associated with COVID-19-related pneumonia, present only in one control patient with non-COVID-19-related pneumonia. Importantly, transition aspects between embolic fat and hyaline membranes were also observed. Conclusions This study confirms the lung fat embolism in COVID-19+ patients and describes for the first time novel COVID-19-related features possibly underlying the unfavorable prognosis in people with COVID-19 and obesity.